Synthesis and characterization of nanoporous biphasic calcium phosphate - Mohammad, Nur Farahiyah; Koo, Li Mei; Mohd Riza, Mohd Roslan; Md Saleh, Siti Shuhadah; Mohd Daud, Farah Diana (IOP Publishing Ltd, 2021)
For the past few years, many researchers are focusing on biomaterials fabrication in porous form. The research on porous calcium phosphate has been investigated due to its excellent biocompatibility and better osseointegration. This research paper presented nanoporous biphasic calcium phosphate (BCP) synthesised using chemical precipitation method. Triblock co-polymer F127 was used as pore directing agent. The chemical compositions of pure BCP samples were examined using X-ray diffraction (XRD) analysis which shows common peak of BCP. The pore size distribution (PSD) on the other hand shows that the pore size of the samples mainly distributed at 52.8 nm, 49.6 nm and 32 nm. BCP pellets were soaked in phosphates buffered saline (PBS) and distilled water (DW) for 15 days. The pH of the soaking medium decreases throughout the soaking period due to degradation of BCP pellets, which release hydrogen ions into the PBS and distilled water. BCP degrades faster in distilled water than in PBS. After soaking for 15 days, materials were examined with a scanning electron microscope (SEM) to assess the morphological structure before and after in vitro degradation. Apatite formation was discovered on the surface of the BCP pellet that had been immersed in the PBS solution